THE IMPLEMENTATION OF DIGITAL LITERACY TO ENCOURAGE STUDENTS' DEMOCRATIC ENGAGEMENT IN CIVIC EDUCATION LEARNING - Riana Tambunan; Dasim Budimansyah; Cecep Darmawan (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
Civic education serves as a crucial foundation for students' character building, particularly in fostering their understanding of democratic principles. With the advancement of technology, digital literacy has become an essential element that significantly enhances student engagement in democracy. This study aimed to investigate the impact of digital literacy implementation in civic education across three schools in Bandung: SMA Negeri 11, SMA Negeri 22, and SMK Negeri 14. The research involved three civic education teachers, three IT staff, and nine students from these schools as participants. The methodology adopted was qualitative, utilizing data collection techniques such as observations, interviews, and documentation. The findings revealed that integrating digital literacy in civic education at SMA Negeri 11, SMA Negeri 22, and SMK Negeri 14 positively influenced students' participation in democratic activities. However, the results indicated that significant improvements were not achieved across all indicators, particularly in creativity, critical thinking, and collaboration. The study suggests that while digital literacy has the potential to enhance civic education, further efforts are required to optimize its benefits comprehensively. Overall, the research highlights the need for innovative approaches to effectively integrate digital literacy in civic education to foster a more engaged and democratically active student body.